Otak Sosial dalam Pendidikan Islam: Kajian Pemikiran Daniel Goleman - Wijaya, Bagus Adi; Suyadi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Social Intelligence, Daniel Goleman in his work, social intelligence, reveals that social knowledge is separated into two classes, namely special social concerns and social positions. Current Islamic education is rarely linked to the brain framework or neuroscience. Meanwhile, from one side, according to Pasiak, the school itself follows neuroscience related to efforts to improve students' brains. Call it the accelerated learning hypothesis, quantum learning, the brain being put together advances thus. Despite these problems, Islamic teaching today is considered more as an exchange of information, underscoring the achievement of mental domination. The aim of this research is to examine in more depth the role and function of the brain in humans. More specifically, how the brain is used as the basis for character education carried out by educators so that the education carried out is successful as expected. This research attempts to examine this problem from an Islamic perspective. This exploration is a subjective examination in the context of writing a survey. This research uses literature research that discusses the importance of the topic and compares the results with findings in other research on similar topics and ultimately produces an idea. To obtain data the author used sources found in libraries such as books, journals and the internet. Based on this study, the social brain can be optimized by training students' attitudes and manners and developing social sensitivity with an Islamic material approach.